La gestión administrativa para el fortalecimiento organizacional de la Federación Deportiva Provincial de Orellana. - Astudillo Fuelpas, Bryan Stiwar (2023)
The “Federación Deportiva Provincial of Orellana”, throughout its institutional life, has not had technological tools to help in the organization and storage of information. The purpose of this research is to understand how administrative management affects organizational strengthening. For the above mentioned, two types of research were applied, descriptive, which allows us to understand the essential aspects of the variables, concepts and their development, and mainly to know how is the current situation of the administrative management, on the other hand the field research that allowed us to be first hand knowing the activities that are carried out within this sports entity. The research was applied to books, internet sites, scientific magazines and degree works, with the information obtained a survey was applied to the personnel of the entity, so the variables of the research were developed, to have a diagnosis of the administrative management and to know the incidence in the organizational strengthening. The development of this research will be detailed in chapters, the first three chapters contain introduction, theoretical framework and methodology. The last three chapters contain the results and discussion, conclusions, recommendations and proposal.